Jewish American and Holocaust literature : representation in the postmodern world - Berger, Alan L., 1939-; Cronin, Gloria L., 1947- (SUNY series in modern Jewish literature and culture., 2004)
"Challenging the notion that Jewish American and Holocaust literature have exhausted their limits, this volume reexamines these closely linked traditions in light of recent postmodern theory. Composed against the tumultuous background of great cultural transition and unprecedented state-sponsored systematic murder, Jewish American and Holocaust literature both address the concerns of postmodern human existence in extremis. In addition to exploring how various mythic and literary themes are deconstructed in the lurid light of Auschwitz, this book provides critical reassessments of Saul Bellow, Bernard Malamud, and Philip Roth, as well as contemporary, Jewish American writers who are extending this vibrant tradition into the new millennium. These essays deepen and enrich our understanding of the Jewish literary tradition and the implications of the Shoah."--Jacket